A14 Arginine methylation of huntingtin is a novel post-translational modification that impacts huntington's disease pathogenesis. (September 2018) - Migazzi, Alice; Tripathy, Debasmita; Scaramuzzino, Chiara; Pandey, Udai Bhan; Saudou, Frédéric; Pennuto, Maria; Basso, Manuela
Abstract : Background: Huntington's disease (HD) is a fatal neurodegenerative disorder characterized by the loss of striatal and cortical neurons. HD is caused by an abnormal polyglutamine (polyQ) expansion in huntingtin protein (HTT). Arginine methylation is a post-translational modification (PTM) catalyzed by protein arginine methyltransferases (PRMTs) with a key role in the pathogenesis of polyglutamine diseases. However, its role in HD remains to be elucidated. Aims: The aim of our work is to understand whether HTT is methylated by PRMTs and how this PTM affects the toxicity of mutant HTT. Methods: We analyzed arginine methylation of HTT by mass spectrometry of mouse brain extracts and in vitro methylation assays. The interaction of wild-type or polyQ-HTT with PRMTs was investigated through immunoprecipitation and proximity ligation assay in immortalized striatal cells. Finally, we undertook a loss-of-function and gain-of-function approach both in vitro and in vivo to assess the role of PRMTs and arginine methylation in HD. Results: We found that HTT is methylated at specific arginine residues in the brain of normal mice. HTT colocalizes and forms a complex with specific members of the PRMT family. Importantly, the polyglutamine expansion in HTT reduces the interaction with the PRMTs. Loss of PRMT function in striatal cells expressing polyQ-HTT exacerbates toxicity, and the expression of a methylation-defective mutant of HTT decreases the survival of primary cortical neurons. Conversely, gain of PRMT function attenuates striatal cell death and suppresses polyQ-HTT-mediated lethality in HD flies. Conclusions: These results suggest that arginine methylation plays a key role in HD pathogenesis. Particularly, PRMT-mediated arginine methylation of HTT is protective in HD.